NMR Hyperpolarization Techniques of Gases. Issue 4 (7th December 2016) - Barskiy, Danila A.; Coffey, Aaron M.; Nikolaou, Panayiotis; Mikhaylov, Dmitry M.; Goodson, Boyd M.; Branca, Rosa T.; Lu, George J.; Shapiro, Mikhail G.; Telkki, Ville‐Veikko; Zhivonitko, Vladimir V.; Koptyug, Igor V.; Salnikov, Oleg G.; et al.
Abstract: Invited for the cover of this issue is a group of researchers coordinated by E. Y. Chekmenev from Vanderbilt University. The image depicts hyperpolarized Xe‐129 and parahydrogen gases and their MRI applications. Read the full text of the article at10.1002/chem.201603884 . Abstract : " We hope that this contribution will provide an overview on the fundamental advances in Physical Chemistry and Catalysis to enable the hyperpolarization processes/tools to be used for completely new applications ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 725 ff. (DOI:10.1002/chem.201603884 ).